Pushover analysis and failure pattern of a typical masonry residential building in Bosnia and Herzegovina - Ademović, Naida (2013)
The paper discusses the behavior of a typical masonry building in Bosnia and Herzegovina built in the 50’s without any seismic guidelines. A global numerical model of the building has been built and masonry material has been simulated as nonlinear. Additionally, calculations done with a "less" sophisticated model are in a good correlation with the finite element method (FEM) calculations. It was able to "grasp" the damage pattern; not as detailed as in the FEM calculations, but still quite good. On the basis of this it may be concluded that in this case calculation with Frame by Macro Elements (FME) program could be recommended for future analysis of this type of structures, having quite good results with a less computation time. However, in the need for more precise results FEM should be utilized.